Conflicto y desigualdad : Relaciones de trabajo doméstico en Salta actual - Ferro, Gabriela Karen (2017)
La frontera de Uruguay con o Brasil ha sido históricamente identificada como una región con los peores indicadores socioeconómicos del país. Por otro lado, la frontera de Uruguay con o Brasil es una región bilingüe, con una situación considerada de diglosia a partir del primer campo de estudios lingüísticos. Esto nos hace preguntarnos si las diferencias de los resultados educativos tienen que ver específicamente con el uso del "portuñol" por parte de los estudiantes que viven en la frontera. El objetivo de esta investigación es analizar el efecto aislado de ser hablante de "portuñol" y vivir en la frontera, agregando a los determinantes educativos clásicos, factores lingüísticos usando microdatos de PISA 2009. Los resultados permiten confirmar la hipótesis de una desigualdad lingüística a un nivel personal.
The Uruguayan borderline with Brazil has historically been identified as a region with the worst socioeconomic indicators of the country. On the other side, Uruguayan borderline with Brazil is a bilingual region, with a categorized situation of diglossia from the earliest linguistic studies. This makes us wonder if differences on educational results are related with the use of ?portuñol? on behalf of the Uruguayan borderline students. The aim of this research is to analyze the isolated effect of being a "portuñol" speaker and live in the borderline, over a standard model of educational inequality (social class, gender, type of educational institution). In order to achieve this we generated a Hierarchical Linear Model in two levels: students and schools, adding to the classical educational determinants linguistic factors, using microdata of PISA 2009. The results allow us to confirm the hypothesis of a linguistic inequality on an individual level.
Keywords: Desigualdades educativas; Factores lingüísticos; Education inequality; Linguistic factors